The relationship between first trimester systemic inflammatory markers and elevated uterine artery pulsatility index - Lutfiye Uygur (SERNEV, 2023)
Introduction: Preeclampsia is a serious complication of pregnancy leading to maternal and perinatal morbidity and mortality. The etiopathogenesis still remains unsolved, however, various theories currently become well-proved. The leading etiopathogenetic mechanisms are impaired placentation, and placental hypoxia, immune mechanisms, systemic inflammatory reaction, endothelial damage and maternal cardiovascular maladaptation. These mechanisms overlap and induce each other. There are some preventive interventions only if the patients at high-risk are identified timely. This study aimed to investigate the relationship between the inflammatory pathway and placental insufficiency in the first trimester, utilizing the clinical markers of both. It also aims to find out a cheap and easy test to identify those who absolutely need to undergo a comprehensive risk assessment.Methods: This retrospective observational study included 28 patients with high uterine artery resistance (pulsatility index gt;90th centile) in the first trimester as study group and 67 patients with normal uterine artery resistance in the first trimester as control group. The two groups were compared in terms of risk factors for preeclampsia. Neutrophil/lymphocyte ratio and platelet/lymphocyte ratio as systemic inflammatory markers were compared between the groups. ROC analysis was performed to obtain a cut-off value for predicting high uterine artery pulsatility index.Results: Demographic data, anamnestic and examination risk factors for preeclampsia did not differ between the groups. However, neutrophil/lymphocyte ratio and platelet/lymphocyte ratio were significantly higher in the patients with uterine artery pulsatility index above 90th centile. A cut off value of 3.58 and 136.9 of Neutrophil/lymphocyte ratio and platelet/lymphocyte ratio, respectively were determined for predicting first trimester uterine artery pulsatility index above 90th centile.Conclusions: Neutrophil/lymphocyte and platelet/lymphocyte ratio can simply be used to identify the patients who need referral for uterine artery doppler assessment.Keywords: preeclampsia, uterine artery, pulsatil flow, neutrophil, lymphocyte, placenta